Polychlorinated biphenyls and dibenzofurans increased abnormal sperm morphology without alterations in aneuploidy: The Yucheng study. (December 2016) - Hsu, Ping-Chi; Li, Ming-Chieh; Lee, Yeu-Chin; Kuo, Pao-Lin; Guo, Yueliang Leon
Abstract: In 1979, more than 2000 persons ingested rice oil contaminated with polychlorinated biphenyls and polychlorinated dibenzofurans; this event was called the "Yucheng accident." An increased percentage of oligospermia, reduced ability of sperm to penetrate oocytes, and reduced percentage of male offspring were reported in Yucheng men. This study examined whether the sperm sex ratio and chromosome aneuploidy are responsible for our observed findings in Yucheng men. In 1999–2000, Yucheng men and their neighborhood referents aged 37–50 years were recruited for physical examination, followed by semen analysis. The semen samples were analyzed for chromosomal aneuploidy through fluorescent in situ hybridization according to an established procedure in our laboratory. A total of 50 Yucheng men and 34 neighborhood referents volunteered to participate in the study. Although abnormal morphology was mildly increased, no differences were observed in sperm percentages, with normal numbers of chromosomes X, Y, and 8 in the two groups. The percentage of sperm with aneuploidy of the sex chromosomes or chromosome 8 and of that with diploidy did not vary between both groups. The normal X/Y sperm ratio was not different between the groups. However, among Yucheng men, 8% had a normal X/Y sperm ratio of >1.4, and no neighborhood referent showed such an elevated X/Y ratio. Chromosomal aneuploidy was not elevated in Yucheng men. The mechanisms underlying the reduced sperm capability of oocyte penetration and changed offspring sex ratio in Yucheng men remain undetermined. Highlights: The study cohort has been exposed to high doses of dioxin-like chemicals. Abnormal morphology was found in sperm among Yucheng men. Sperm chromosome aneuploidy was not elevated among Yucheng men. Disproportional reduction of normal Y sperm was not observed in Yucheng men.